Experimental and numerical study of the natural convection from a heated horizontal cylinder - Atayilmaz, S. Oezguer; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Natural convection heat transfer from a horizontal cylinder is studied experimentally and numerically. Experimental study had taken place in different environmental temperature in a conditioned room which can be maintained at a stable required value and inside a sufficiently designed test cabin. The environmental and cylinder surface temperatures varied between 10 degrees C-40 degrees C and 20 degrees C-60 degrees C respectively. In the experimental study, two cylinders having different diameters of 4.8 mm-9.45 mm are used and constant heat flux was applied. On the basis of the experimental data, a correlation for the average Nusselt number over the cylinder is proposed in the range of 7.4 10(1) < Ra<3.4 10(3). The proposed correlation is compared with the well known correlations on natural convection heat transfer from a horizontal cylinder in the specified range of Rayleigh number, and it is shown that the results are in satisfactory agreement. The problem is also investigated numerically. The experimental data and the numerical results fall in +/- 20% band. The numerical results obtained in this study are also compared with the results of Merkin. The characteristics of trend lines are similar. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Heat transfer; Horizontal cylinder; CFD; EQUATIONS; LAMINAR; SURFACE; Thermodynamics; Mechanics